Kitab Suci dan Hoax: Pandangan Alquran dalam Menyikapi Berita Bohong - Luthfi Maulana (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2017)
The raising of hoax phenomenon in the social media is very excessive, especially the impact has been divisive Muslims, whereas the roots of the emergence of the hoax itself is nothing but the influence of global development and the advancement of science and technology, so that humans are pampered with a variety of sophisticated facilities, these facilities cause human beings entitled to freedom of expression. It is this freedom which gives birth to human communication with others indefinitely, even with the media of a person free to express public opinion, through this, one becomes free in exploring the interests of each, especially in realizing a mission of existence by the interests of a particular group, on this basis, regardless of how the impact of the hoax itself works, the groups produce and circulate the hoax news in the public sphere. In response, this study focuses on the Quranic view of the phenomenon of hoax or hoax. Through this descriptive method, this study confirms that the Qur'an as a guideline for Muslims needs to be re-dialled to the Islamic society of today, so through the Qur'an we can see how the hoax itself has been described in it, and how we as Muslims can work to avoid the plague of the hoax itself.